ANALISIS FAKTOR PENYEBAB KESULITAN BELAJAR PADA PEMBELAJARAN BAHASA JAWA KELAS V SD MUHAMMADIYAH BAUSASRAN II YOGYAKARTA - Serli Mahardika; Fery Setyaningrum (Universitas Ahmad Dahlan, 2020)
ABSTRACTThe purpose of this research is to determine the learning difficulties of students in learning Javanese and the factors that cause learning difficulties of students in learning Javanese in class V SD Muhammadiyah Bausasran II Yogyakarta. This type of research is qualitative research with a case study approach. The research subjects consisted of the principal, the class V homeroom teacher, and the fifth grade students. The object of the study was to observe those related to student learning difficulties in the fifth grade Javanese learning of SD Muhammadiyah Bausasran II Yogyakarta. The data collection techniques used were interviews and document review. The validity of the data used source and method triangulation techniques. The data analysis technique used the Miles and Huberman Model with the stages of data reduction, data presentation, and conclusions. The results showed that the factors causing student learning difficulties in Javanese learning can be seen from several types of student learning difficulties, including: difficulties in academic tasks, low learning achievement far below certainty of intelligence, learning disabilities, Learning Disfunction, and Under Achiever. While the factors causing student learning difficulties are internal factors seen from several internal factors that cause student learning difficulties, namely: attitudes towards learning, motivation, interests, social adjustment, students' intelligence level, and physical condition. Teachers of SD Muhammadiyah Bausasran II Yogyakarta have taken action against students who have difficulty learning the teacher teaches using a variety of methods.Â